Integrated Science Learning for Sustainable Development: A Systematic Literature Review of Models, Impacts, and Future Directions - Ratih Dwi Istirahayu; Nurasyah Dewi Napitupulu (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study aims to analyze the development of integrated science learning in the context of Education for Sustainable Development (ESD) through a systematic literature review. The study focuses on identifying dominant integration models, examining their implementation, and exploring their impact and research gaps. A systematic literature review approach was employed following PRISMA guidelines. Data were collected from the Scopus database using predefined search criteria, resulting in 20 selected articles published between 2016 and 2026. Data were extracted using a structured matrix and analyzed through qualitative content analysis and thematic synthesis. The findings reveal that integrated science learning is primarily implemented through transdisciplinary, STEAM-based, and interdisciplinary approaches. These approaches show positive impacts on students’ cognitive, affective, and skill-based outcomes, particularly in enhancing critical thinking, collaboration, and problem-solving abilities. However, the implementation remains inconsistent, with challenges related to curriculum structure, teacher readiness, and assessment practices. Furthermore, the integration of ESD is often implicit rather than systematically embedded, and the measurement of sustainability competencies remains limited. This study highlights the need for more coherent and operational models that integrate curriculum structure, real-world context, and sustainability orientation. The findings provide important implications for the development of integrated science learning frameworks that support sustainable development in education.